COMBINING ABILITY ANALYSIS OF YIELD AND FIBER QUALITY TRAITS UNDER NORMAL AND WATER DEFICIT CONDITION IN GOSSYPIM HIRSUTUM L. - W. S. Chattha; A. Shakeel; T. A. Malik; M. F. Saleem; H. M. Akram; M. Yaseen; M. Naeem (Journal of Animal and Plant Sciences, 2018)
Present investigation was conducted to study the genetic basis of seed cotton yield and fiber quality traits in cotton under normal and water deficit condition. 30F crosses along with 13 parents were planted under two stress levels i.e. normal 1 and water-deficit conditions in field. The best general combiners under normal condition were FH-153, FH-159 and FH- 207, while FH-207, FH-322 and NS-131 were the best general combiner for seed cotton yield, under water-deficit conditions. For fibre quality traits, VH-291 & NS-131 and S-15 & FH-207 were best general combiners under normal irrigation and water deficit condition, respectively. Variance due to specific combining ability was greater for the traits indicating the dominant role of non-additive genes under normal and water-deficit condition. The best specific combiner for fiber quality traits were FH-159 × KZ-191 and VH-291 × NS-131 under normal irrigation while under water deficit condition the best specific combiners were FH-207 × AA-703 and VH-291 × NS-131. Under normal condition the crosses FH-153 × NS-131, FH-159 × KZ-191, IR-6 × KZ-191, S-15 × NS-131 and VH-289 × AA-703 were the best specific combiner for seed cotton yield and the crosses FH-207 × KZ-191, MNH-886 × AA-703 and S-15 × NS-131 showed high specific combining ability effects for seed cotton yield under water-deficit condition. These crosses might be used in variety development program for water deficit areas of Pakistan. Non additive variation for all the traits suggests possibility of using this material for hybrid development in cotton. that are controlled by additive component which indicate
Keywords: Combining ability; Line × tester analysis and seed cotton yield.